The Development of Interactive Multimedia of TPACK-Based Buffer Solution Material Using Google Sites to Increase Student’s Interest in Learning - Zalfa, Laudza Keisha; Haryanto, Haryanto; Epinur, Epinur (ALACRITY : Journal of Education, 2024)
Education is one of the important aspects of life. Currently, technology in Indonesia is progressing very rapidly. One of the fields that cannot be separated from the influence of technology is education. Chemistry is one of the important subjects to study in high school because chemistry can improve thinking skills and stimulate student’s creative mindset. One of the materials in chemistry is buffer solutions. Buffer solution materials are often considered difficult by students because of their complex nature and use a lot of mathematical calculations. The many problems and difficulties in learning certainly make student’s interest in learning low. The purpose of this study is to analyze the effectiveness of TPACK-based interactive multimedia Google Sites in increasing student’s interest in learning about buffer solution materials. The method used in this study is Literature Review or narrative literature review which aims to analyze, evaluate and synthesize all information from previous research that is relevant to the research topic. Literacy data search websites such as Mendeley and Google Scholar are used to search for articles used. The articles used are articles published between 2020 and 2024. The results of this study can be concluded that using TPACK-based interactive Google Sites multimedia as a learning media can increase student’s interest in learning.